2018
DOI: 10.2139/ssrn.3285205
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Welfare of Intermediation in Vertical Markets

Abstract: We empirically investigate the welfare implications of intermediaries in oligopolistic markets, where intermediaries offer additional services to differentiate their products from the ones of the manufacturers. Our identification strategy exploits the unique circumstance that, in the outdoors advertising industry, there are two distribution channels: consumers can purchase the product either directly from manufacturers, or through intermediaries. We specify a differentiated products' equilibrium model, and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 106 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…There has been growing interest from empirical researchers in analyzing the role of intermediaries, but most of these studies focus on intermediaries' roles of resolving search frictions. Recent examples include Hendel, Nevo, and Ortalo-Magné (2009), Gavazza (2016), Salz (2017), and Donna et al (2018). One exception is Galenianos and Gavazza (2017), who estimate a model of cocaine buyers and sellers and show that reputation concerns help support an equilibrium where the dealer offers high-quality drugs in the presence of asymmetric information.…”
Section: Introductionmentioning
confidence: 99%
“…There has been growing interest from empirical researchers in analyzing the role of intermediaries, but most of these studies focus on intermediaries' roles of resolving search frictions. Recent examples include Hendel, Nevo, and Ortalo-Magné (2009), Gavazza (2016), Salz (2017), and Donna et al (2018). One exception is Galenianos and Gavazza (2017), who estimate a model of cocaine buyers and sellers and show that reputation concerns help support an equilibrium where the dealer offers high-quality drugs in the presence of asymmetric information.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent work by De Los Santos et al (2012) and Honka and Chintagunta (2017) has shown that, for books and car insurance sold online, observed consumer search patterns are consistent with simultaneous search. 1 Furthermore, because search decisions do not depend on search outcomes when searching simultaneously, obtaining closed-form expressions for purchase probabilities and market shares is relatively easy and this has made models of simultaneous search for differentiated products popular in recent empirical work (see, e.g., De Los Santos et al, 2012;Honka, 2014;Moraga-González et al, 2015;Pires, 2016;Ershov, 2018;Murry and Zhou, 2020;Lin and Wildenbeest, 2020;and Donna et al, 2019).…”
mentioning
confidence: 99%